Plasticity and Signal Representation in the Auditory System - Syka, Josef; Merzenich, Michael M. (Springer US : Imprint: Springer, 2005)
This volume summarizes the state of development of auditory system neuroscience. This field is in an era of remarkable progress, particularly in the field of plasticity of the auditory system. New advances in understanding auditory system plasticity, based substantially on a large and growing body of results from animal experiments, are related to innumerable new insights into the physiology and pathology of speech and music perception and production generated by behavioral studies, and from the application of modern brain imaging techniques. We are living in an especially exciting period of research, marked by an almost astounding rate of advance in the development of our understanding of the hearing brain. The extraordinary series of reports published in this book document this rapid, further advance.